Independent contracting : succeeding as a contract professional in Australia - Green, Ruth.; Petty, John.; Woodd, Janet; Robinson, Kate. (Sydney : Pearson Education, 2000)
This book is about: Taking the plunge; Legal identity; Business identity; Financing your business; Attracting clients; Getting the contract right; ...
Keywords: Australia; Business; Management; Labor; Independent contractors -- Australia; Labor contract -- Australia; New business enterprises -- Management -- Handbooks, manuals, etc